Warenhuis As a National Cultural Heritage Site A Legacy of The Dutch Colonial Era In Medan - N Najuah; Fitri Nurjihan; Dania Amanda; Esa Indriyani Br Bangun; Lutfia Khairani Pane (International Journal of Science and Environment (IJSE), 2026)
At the beginning of its development, Medan City was a small village called "Medan Putri". After that, workers from the port who had run out of contracts began to come to the village, precisely in the Kesawan area, to trade. Warenhuis is a heritage building from the Dutch Colonial Period which was once victorious and is a silent witness to the journey of the Dutch people while ruling this region, namely the city of Medan. One type of research used in this paper is literature research, which is included in the category of library research. In continuation of this research, the approach method in this research uses a historical method with a descriptive approach which is used to create a picture of an event or event. Writing history not only records events in chronological order, but also requires in-depth analysis supported by relevant theories. Warenhuis is one of the buildings that has been neglected in recent years. If you look at its shape, it will be in accordance with the functional space requirements of the performing arts building and gallery for historical objects. When the building was first built, this building functioned as a Dutch chamber of commerce, then it changed its function as an opera house and after Indonesia became independent this building became an office building. In the present, Warenhuis has been taken over and managed by the government. During its revitalization period, it will be transformed into the Medan City Education Center and Painting Art Gallery.